2021
DOI: 10.3390/nu13030881
|View full text |Cite
|
Sign up to set email alerts
|

The Western Dietary Pattern Combined with Vancomycin-Mediated Changes to the Gut Microbiome Exacerbates Colitis Severity and Colon Tumorigenesis

Abstract: Previous work by our group using a mouse model of inflammation-associated colorectal cancer (CAC) showed that the total Western diet (TWD) promoted colon tumor development. Others have also shown that vancomycin-mediated changes to the gut microbiome increased colorectal cancer (CRC). Therefore, the objective of this study was to determine the impact of vancomycin on colon tumorigenesis in the context of a standard mouse diet or the TWD. A 2 × 2 factorial design was used, in which C57Bl/6J mice were fed either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
3
4
0
Order By: Relevance
“…As observed repeatedly in this murine model of CAC [ 9 , 22 , 32 ], mice fed the TWD (irrespective of FMT source) had shorter colon length, more severe colitis symptoms, higher inflammation and mucosa injury scores, higher tumor multiplicity, larger average tumor volume, and higher tumor burden compared to their AIN-fed counterparts. Interestingly, in this experiment, we also observed a marked increase in colon tumor incidence in the TWD-fed recipient mice.…”
Section: Discussionsupporting
confidence: 58%
“…As observed repeatedly in this murine model of CAC [ 9 , 22 , 32 ], mice fed the TWD (irrespective of FMT source) had shorter colon length, more severe colitis symptoms, higher inflammation and mucosa injury scores, higher tumor multiplicity, larger average tumor volume, and higher tumor burden compared to their AIN-fed counterparts. Interestingly, in this experiment, we also observed a marked increase in colon tumor incidence in the TWD-fed recipient mice.…”
Section: Discussionsupporting
confidence: 58%
“…Consumption of a rodent diet that emulates the typical American pattern with respect to macro-and micronutrient profiles has been repeatedly shown to enhance symptoms of colitis, inflammatory cell infiltration, mucosal injury and tumor development in murine models of colitis-associated colorectal cancer [12,35]. Herein, we report the findings from the first investigation to explore the purported benefit of dietary supplementation with BRB for gut health and modulation of the gut microbiome in a mouse model of Westerndiet enhanced colitis and colitis-associated colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were housed in a specific pathogen-free vivarium in the Laboratory Animal Research Center (LARC) at Utah State University, an AAALAC-approved facility. To be consistent with previous work on the role of the TWD in CAC [12,13,35,36], male C57BL/6J mice were obtained from Jackson Laboratories (Bar Harbor, ME) at five weeks of age. Mice were group-housed in sterile microisolator cages with Bed-o'Cobs ® 1 /4 bedding (Andersons, Cincinnati, OH, USA) supplied with HEPA-filtered microisolator cages in an IVC Air Handling Solutions ventilated housing system (Tecniplast, Buguggiate, Italy).…”
Section: Animals and Experimental Dietsmentioning
confidence: 99%
“…Antibiotics have proven their ability to inhibit the development of colitis [ 45 , 46 ]. Experimentally, oral vancomycin is used to evaluate changes during chronic disease models due to the lack of systemic absorption and its localized effects on the gut [ 47 ]. In this study, after seven days of treatment, our results indicated that oral vancomycin treatment showed higher efficiency than FMT and LBP freeze-dried powder.…”
Section: Discussionmentioning
confidence: 99%